BODY DISSATISFACTION, KECEMASAN SOSIAL PADA REMAJA PEREMPUAN - Maydela Putri; Rizqi Amalia Aprianty (Fakultas Psikologi Universitas Wijaya Putra, 2023)
When interacting socially, not all teenage girls will feel safe, because in reality there are still many teenage girls who feel anxious and uncomfortable when dealing directly with their surroundings and thus experience social anxiety. One of the factors that influences it is body dissatisfaction. This research aims to determine the effect of body dissatisfaction on social anxiety in adolescent girls. High levels of body dissatisfaction can lead to serious consequences, such as eating disorders, depression, and anxiety. Additionally, social anxiety can limit social participation and affect interpersonal relationships. Sampling used the Nonprobability Sampling technique with the Incidental Sampling method. This research involved 347 teenage girls aged 12-21 years. The measuring instruments used in this research were the body dissatisfaction scale (29 items, α = 0.964) and the social anxiety scale (26 items, α = 0.922). The research results show that there is a significant influence of body dissatisfaction on social anxiety in female adolescents (p = 0.000 < 0.05) with an influence size of R square = 45.4% and the direction of the relationship between the two variables is positive with a value of r = 0.674. This means that if body dissatisfaction increases, social anxiety will also increase and vice versa, if body dissatisfaction decreases, social anxiety will also decrease.